Andrological Points Classification (CAP) Nelore Bulls (Bos Taurus Indicus) Of Different Ages, Kept in Reproduction Central (Global Journal of Medical Research, 2023)
The objective of this study was to evaluate the reproductive potential of Nellore bulls at different ages using the Andrological Points Classification system and to analyze the physical and morphological characteristics of the semen when submitted to the cryopreservation protocol Thus 15 Nellore bulls were evaluated divided into three groups according to age The first group consisted of bulls aged 4 years the second group of bulls aged 5 to 7 years and the third group of bulls aged 8 to 10 years From the evaluations performed biometrics testicular and semen morphology were relevant to determine the andrological classification by points CAP index For this purpose the semen was collected using the electroejaculation method And the results were expressed as mean and standard deviation The variables were submitted to ANOVA Tukey and Pearson s correlation tests with the differences between the groups being significant at the p 0 05 level The results describe differences between the groups and in the sperm viability between the groups when the samples are submitted to different moments of evaluation In natura post-thaw and thermoresistance test It is concluded that the Nellore breed presents variation in the sperm quality with a very small loss on the older ones
Keywords: bovine; males; production; sanity